A semi-empirical design parameter for determining the inelastic strike-face mass fraction of soft armor targets. (March 2019) - Guo, Zherui; Chen, Weinong; Zheng, James
Abstract: At the ballistic limit velocity of a soft armor target pack, the impact response was shown to be decoupled in the thickness direction, with the initial few plies behaving in an inelastic fashion while the remaining plies dissipate energy via elastic strain modes. Since these initial plies only contribute to energy absorption via inelastic kinetic energy transfer, these plies may be replaced with another material with desirable properties, such as low costs or high shear strengths. The behavior of these diphasic armors has been shown in previous works to be varied depending on the type and the amount of strike face material that was replaced. However, there is a limited amount of published literature investigating this phenomenon. In this study, a framework is proposed to estimate the inelastic strike-face mass ratio as a function of the overall system areal density ratio to provide a preliminary design tool for diphasic armors.